Alterations of amplitude of low-frequency fluctuation in treatment-resistant versus non-treatment-resistant depression patients - Zhang A; Li G; Yang C; Liu P; Wang Y; Kang L; Wang Y; Zhang K (Neuropsychiatric Disease and Treatment, 2019)
Aixia Zhang,1,2 Gaizhi Li,1 Chunxia Yang,1 Penghong Liu,2 Yanfang Wang,1 Lijun Kang,2 Yuchen Wang,2 Kerang Zhang11Department of Psychiatry, First Hospital of Shanxi Medical University, Taiyuan 030001, People’s Republic of China; 2Shanxi Medical University, Taiyuan 030001, People’s Republic of ChinaPurpose: We used parcellation based on 264 putative functional areas to explore the difference of amplitude of low-frequency fluctuation (ALFF) between refractory depression and non-refractory depression patients.Patients and methods: Sixty first episode drug-naive patients with major depressive disorder (MDD) and 20 healthy controls (HCs) were recruited in this study; the MDD group was divided into a refractory depression (TRD) group (n=15) and a non-refractory depression (non-TRD) group (n=18) according to the treatment effect following up for 2 years. All the subjects underwent magnetic resonance imaging scanning and performed the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) and all the patients with MDD finished the 17-item Hamilton Depression Rating Scale (HAMD17). We used a parcellation based on 264 putative functional areas to explore the difference of ALFF measures in the three groups. The correlation between the abnormal ALFF value and characteristics of MDD was examined.Results: RBANS total scores and index scores in the HCs were significantly different from that of the MDD group. HAMD-17 in the TRD group was significantly higher than that of non-TRD group. Relative to HCs, MDD groups showed significantly lower ALFF within the right default mode network, which was positively correlated with the immediate memory and language in the MDD group. Compared with the non-TRD group, the TRD group showed higher ALFF in the right sensory/somatomotor hand, right auditory and left default mode network.Conclusion: Dysfunction of the somatosensory areas, right auditory and left default mode network may be a marker for specific psychopathology symptoms of TRD.Keywords: amplitude of low frequency fluctuation, refractory depression, 264 putative functional area